La transdisciplinariedad como eje transversal de la docencia universitaria: un constructo transmetodológico contrarresistencia (2021)
Rhizomatic research from deconstruction as a transmethod supports transdisciplinarity as a transversal axis of university teaching, a counter-resistance transmethodological construct, as a complex research objective. It is deconstructed by insubordinating the disciplines in universities to question the individual object in teaching-research and, then, in a hopeful reconstruction, we will mainstream the transdisciplinarity in university teaching that lies in a transcomplex decolonial education, deeply inclusive that attends to complex processes of the human being and his shaping as a citizen of the world in a planetary decoloniality, which favors transmethodologies with transmethods that make complex the methods, such as critical transdisciplinary research and complex participatory action research.